STRATEGI INDONESIA DALAM MENINGKATKAN NILAI EKSPOR VIRGIN COCONUT OIL (VCO) KE TIONGKOK TAHUN 2015-2018 - Novika Sari; Yusnarida Eka Nizmi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is conduct to analyze the strategy of Indonesian government to increase export value of Virgin Coconut Oil (VCO) to Tiongkok by elaborating the dynamic bilateral relationship of Indonesia – Tiongkok since the independence of Indonesia up till nowdays especially in trading relationship and elaborating the general description of VCO production in Indonesia. This research hopefully would be a source of information and insights to many people as well as the motivation to accomplish perfection for the next research. The research was conducted from 2015-2018. This research used qualitative researcdesing as the research methodology. The type of the data was secondary data, gathered by doing research such as reading and writing as well as processing and gathering the research material through books, journals, printed media, electronics media and the other legal or validated sources. The result of the research shows that some strategies done by Indonesia to increase the export value of VCO to Tiongkokhave done well and increased the export value of VCO for the next year. Since 2009 the value of Indonesia's VCO export kept going up and it went done in 2015. As the result, Indonesia applied various strategies to increase the export of VCO to Tiongkok , the strategy was succeed ro increase the export value of VCO to Tiongkok in 2016-2018.Keyword: Export, Qualitative, Strategy, VCO